Manajemen Pembinaan Guru Guna Meningkatkan Mutu Pembelajaran (Studi Kasus PKBM Zahratul Fikri Ciparay Kabupaten Bandung) - Soro, Suharyanto H; Susilawati, Leli; Permana, Yan Yan Yoga; Sobirin, Wahyu (LPPM Institut Pendidikan Nusantara Global, 2024)
Achieving and improving the quality of education is a hope, desire, demand and view that not everyone can fulfill. A teacher is an educator who is a determining factor in the success of a nation's quality, especially in efforts to improve the quality of education. This research aims to determine teacher development to improve the quality of learning at the Zahratul Fikri Community Learning Activity Center (PKBM), Ciparay District, Bandung Regency. The approach used is a case study approach. The data collection techniques used are observation, interviews, and documentation studies. The research results show that teacher coaching using data can improve the quality of learning. Teacher development includes: pedagogical competence, personality competence, professional competence, social competence. By coaching teachers, it is hoped that they can (1) improve the teaching climate, (2) improve teaching materials/materials (3) improve learning methods/organization, (4) improve media use (5) improve assessment. The results of the research prove that: Forms of teacher coaching include: conducting educational supervision, conducting principal management training, attending subject workshops and evaluations, attending subject teacher deliberations, taking part in learning media creation training, providing coaching by supervisors, and exemplifying exemplary attitudes (discipline), responsibility, honesty, and other forms of positive characteristics). The factors that influence teacher development include (1) Internal factors such as: teacher personality, teaching ability, discipline, welfare, and work ethic. (2) External factors such as: communication skills and good relations with the community. (3) Supporting factors such as: Facilities and infrastructure. Based on the results of this research, if teacher development is carried out continuously, it can improve the quality of learning, both in terms of process and in terms of results.